The genus Lecithocera (Lepidoptera: Lecithoceridae: Lecithocerinae) in Kenya and Tanzania, with descriptions of six new species - Park, Kyu-Tek; Yu, Tae-Uk; Jeong, Su-Yeon (Zootaxa, 2024)
Six new species of the genus Lecithocera Herrich-Schäffer, 1853 (Lecithocerinae) are described from Kenya and Tanzania: five new species from Tanzania (L. kitulangaroensis Park, sp. nov., L. grisella Park, sp. nov., L. soniana Park, sp. nov., L. triasgonia Park, sp. nov., and L. majorella Park, sp. nov.) and one new species from Kenya (L. naromoruensis Park, sp. nov.). In addition, Lecithocera namizimuensis Park & Heppner, 2023 and L. isomitra Meyrick, 1914, which were described from Malawi, are reported for the first time from Tanzania and Kenya respectively; the male genitalia of L. isomitra are newly described; and the male genitalia of L. sceptrarcha Meyrick, 1920 are illustrated and described for the first time, based on those of the lectotype. Adults and the genitalia of the new species and the first known species are illustrated.